Introduction to physical therapy and patient skills - Dutton, Mark (illustrations, 2014)
Presents an introduction to the art, science, and practice of physical therapy. This book provides a foundation upon which to build a career in the challenging yet rewarding field of physical therapy. It provides the conceptual framework necessary to understand every aspect of physical therapy and eventually perform physical therapy intervention.